2002
DOI: 10.1002/pd.224
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of a familial complex chromosomal rearrangement involving chromosomes 5, 10, 16 and 18

Abstract: We report one case of a familial complex chromosomal rearrangement (CCR) involving four different chromosomes 5, 10, 16 and 18. The CCR was detected prenatally at 20 weeks' gestation because of advanced maternal age and history of recurrent miscarriages. Cytogenetic analysis of cultured amniotic fluid cells with GTG banding showed a 46,XX,t(5;16;10;18)(q13;q22;q11.2;q21) karyotype. Parental cytogenetic study revealed that the mother has the same CCR. RBG banding, high resolution banding and fluorescence in sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…When CCR is reevaluated by using advanced techniques, the number of breakpoints tends to increase over the number that initially was identified by using conventional cytogenetic techniques (22,23). The carriers of CCRs may transmit a balanced or unbalanced karyotype to offspring in the family (24)(25)(26). However, CCR carriers still have a limited chance of having a healthy child.…”
Section: Discussionmentioning
confidence: 97%
“…When CCR is reevaluated by using advanced techniques, the number of breakpoints tends to increase over the number that initially was identified by using conventional cytogenetic techniques (22,23). The carriers of CCRs may transmit a balanced or unbalanced karyotype to offspring in the family (24)(25)(26). However, CCR carriers still have a limited chance of having a healthy child.…”
Section: Discussionmentioning
confidence: 97%
“…These authors divided CCRs in 2 broad groups: one group ≤ 4 breaks and the other group >4 breaks. They observed that most familial CCRs belonged to the group with up to 4 breaks and have been transmitted by a balanced female carrier, whereas most of the de novo CCRs belonged to the group with more than 4 breaks and were of paternal origin [Kousseff et al, 1993;Batista et al, 1994;Joyce et al, 1999;Lee et al, 2002;Grasshoff et al, 2003;Kuechler et al, 2005]. The majority of the reported cases had 4 or less breaks [Pellestor et al, 2011].…”
Section: Definition and Classification Of Ccrsmentioning
confidence: 99%
“…are clinically utilized and have shown significant impact clinical human genetics, especially in diagnosing and counseling familial syndromes e.g. familial CCRs [21], [22] or familial 5p−/CDCs syndrome [23], [24].…”
Section: Introductionmentioning
confidence: 99%